Comparing Word Processing Times in Naming, Lexical Decision, and Progressive Demasking: Evidence from Chronolex - Ferrand, Ludovic; Brysbaert, Marc; Keuleers, Emmanuel; New, Boris; Bonin, Patrick; Méot, Alain; Augustinova, Maria; Pallier, Christophe (Frontiers in Psychology, 2011)
We report performance measures for lexical decision, word naming, and progressive demasking for a large sample of monosyllabic, monomorphemic French words (N = 1,482). We compare the tasks and also examine the impact of word length, word frequency, initial phoneme, orthographic and phonological distance to neighbors, age-of-acquisition, and subjective frequency. Our results show that objective word frequency is by far the most important variable to predict reaction times in lexical decision. For word naming, it is the first phoneme. Progressive demasking was more influenced by a semantic variable (word imageability) than lexical decision, but was also affected to a much greater extent by perceptual variables (word length, first phoneme/letters). This may reduce its usefulness as a psycholinguistic word recognition task.